Formation, Classification, and Properties of Soils at Two Relict Charcoal Hearth Sites in Brandenburg, Germany - Hirsch, Florian; Schneider, Anna; Bauriegel, Albrecht; Raab, Alexandra; Raab, Thomas (Frontiers in Environmental Science, 2018)
Historical charcoal production can have significant effects on soil properties. We studied soils at former charcoal production sites (relict charcoal hearths, RCHs) and compared these soils with undisturbed soil next to the charcoal hearths and four typical soils on similar parent material located at distances between 10 and 70 km from the RCHs. In a landscape typical of the northern German lowland, we found Podsolige Braunerde (WRB: Brunic Arenosols (Protospodic)) outside of the RCHs and soils with a clearly different stratigraphy within the RCHs. The main feature of the soils at both of the studied RCHs is a heterogeneous, charcoal-bearing deposit that is approximately 30 cm thick. No indications of translocation or mineral transformation processes, which form distinct soil horizons after the deposition of anthropogenic material on the RCHs, are present. Except for the differences in color and total carbon content, the soil chemistry of the RCHs hardly differs from that of the soil outside of the charcoal hearth sites. The soil colors and magnetic susceptibility values strongly suggest that the RCH substrates and the underlying topsoil were affected by thermally induced transformation of iron (hydr-)oxides. Although the charring procedure normally requires approximately two weeks, the heating effect only reaches to a maximum depth of 8 cm into the buried soil below the charcoal hearths. The presence of reddish soil and an abrupt increase in magnetic susceptibility in the upper 2 cm of the soil below the charcoal hearths indicate the heat-induced transformation of iron (hydr-)oxides into maghemite. Brighter soil color and an increase in soil organic matter in the lower parts of the buried topsoil demonstrate the combustion of soil organic matter up to 5 cm depth below the RCH. According to the German Guidelines for Soil Mapping, the soils in the RCHs are classified as Regosols above Braunerde (WRB: Spolic Technosols (Arenic)). However, because the anthropogenic features of these soil sediments are disregarded in the German Guidelines for Soil Mapping, we suggest adapting the ‘M’ horizon to permit a jM horizon. Thus, the soils in the RCHs could be classified as Kolluviale Braunerde.